
展开全部
解:原式=2[(x+y)^2-4(x-y)^2]
=2(x+y+2x-2y)(x+y-2x+2y)
=2(3x-y)(-x+3y)
=2(-3x^2+10xy-3y^2)
=-6x^2+20xy-6y^2
=2(x+y+2x-2y)(x+y-2x+2y)
=2(3x-y)(-x+3y)
=2(-3x^2+10xy-3y^2)
=-6x^2+20xy-6y^2
展开全部
2(x+y)^2+8(y-x)^2
=2[(x-y)^2+4xy]+8(y-x)^2
=10(x-y)^2+8xy
=2[(x-y)^2+4xy]+8(y-x)^2
=10(x-y)^2+8xy
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
解:原式=2[(x+y)^2-4(x-y)^2]
=2(x+y+2x-2y)(x+y-2x+2y)
=2(3x-y)(-x+3y)
=2(-3x^2+10xy-3y^2)
=-6x^2+20xy-6y^2
=-2(3x^2-10xy+3y^2)
=2(x+y+2x-2y)(x+y-2x+2y)
=2(3x-y)(-x+3y)
=2(-3x^2+10xy-3y^2)
=-6x^2+20xy-6y^2
=-2(3x^2-10xy+3y^2)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询